THE EFFECT OF AUDIT OPINION, KAP SIZE & FINANCIAL DISTRESS ON AUDITOR SWITCHING - Desi Natalia; Listiya Ike Purnomo (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2020)
This research is examining factors that affect auditor switching. Those factors are audit opinion, KAP size and financial distress. Population of this research are maufacturing companies which are listed in Indonesian Stock Exchange in the years 2013-2017. Total sample in this research are 55 companies using purposive sampling method. The data used is secondary data obtained from the company's financial statements and independent auditor’s report published in the website www.idx.co.id. Data analys by using logistic regression analysis method. Result of this research is Audit Opinion and CPA firm size have significant effect with auditor switching. Meanwhile, financial distress does not have signifiicant effect with auditor switching.